Mathematics in the Social Sciences and Other Essays - Stone, Richard (London: Chapman & Hall, 1966)
It is now generally agreed that mathematical methods are necessary both at the theoretical level, to formulate problems precisely, to draw conclusions from postulates and to gain insight into the workings of complicated processes, and at the applied level, to measure variables, to estimate parameters and to organize the elaborate calculations involved in reaching empirical results. The seventeen essays collected in this book are all illustrations of the belief in this principle. Most of the examples in this literature relate to economics, and more particularly to the computable model of the British economy.
Bibliography: p. [283]-291.
ne 20/03/2018
Loans
Keywords: Economics, Mathematical; Social Sciences